Analisis Penganggaran Biaya Produksi dan Efisiensi Bahan Baku pada Industri Mebel Dhany Furniture di Dukuh Tarub - Eri Susanti; Az Ziky Izzah Ramadhani; Shelly Septiana Luckyta Sari; Brilianti Binugraheni; Muhammad Aditya Yulianto (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2026)
Business actors, particularly micro-scale industries, must properly plan and control production costs to survive amid uncertainty in the business environment. This study analyze the furniture business Dhany Furniture in Boyolali Regency and analyzes its production cost budgeting and efficiency of cost utilization. A descriptive qualitative and quantitative case study approach was employed in this research. Data were collected through documentation and interviews, including information on production cost budgets, raw material usage, direct labor, and factory overhead costs. The results indicate that production cost budgeting at Dhany Furniture has been systematically arranged by classifying costs into raw materials, direct labor, and factory overhead for each type of product, such as minimalist living room chairs, minimalist six-seat dining tables, and beds. The total production cost is most significantly influenced by teak wood raw materials. However, the use of a manual raw material recording system makes production cost control more difficult, resulting in inefficiencies and potential waste. Therefore, although production cost budgeting has been properly designed, production costs at Dhany Furniture have not yet been fully efficient. Improvements in the cost recording and control system are necessary to achieve more accurate determination of the cost of goods manufactured.